The Effectiveness Of E-Government In Improving The Quality Of Public Services: A Case Study Of The Makassar City Government - Muhammad Anas (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This study examines the effectiveness of e-government implementation in improving public service quality in Makassar City Government. The rapid development of information technology has prompted local governments to adopt e-government systems, yet their effectiveness in enhancing public service delivery requires comprehensive evaluation. This research employs a mixed-method approach, combining qualitative and quantitative data collection through interviews with government officials, surveys of 200 citizens, and direct observation of e-government services. The findings reveal that Makassar's e-government initiatives have significantly improved service delivery efficiency, with 75% of users reporting increased satisfaction in public services. However, challenges persist, including digital literacy gaps among citizens and occasional technical infrastructure issues. The study identifies key success factors such as strong leadership commitment, adequate IT infrastructure, and regular system updates. These findings contribute to the growing knowledge on e-government implementation in developing regions and provide practical recommendations for local governments seeking to enhance their digital service delivery systems.